Perancangan Sistem Informasi Terhadap Pelayanan Administrasi Masyarakat Desa Berbasis Web di Kecamatan Seunagan Timur Kabupaten Nagan Raya - Nurhayani; Taufiq Iqbal; Ismail (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Seunagan Timur Subdistrict in Nagan Raya Regency faces challenges in managing village administrative services due to reliance on manual processes and basic applications like Ms. Word and Ms. Excel. These tools can only handle local data, resulting in delayed updates and reduced accuracy of information, which hampers effective and efficient public services. This research aims to design a web-based information system for village administrative services using the waterfall method. The waterfall approach involves several stages: requirements analysis, system design, implementation, testing, and maintenance. The results indicate that the web-based information system improves data management efficiency, simplifies data retrieval, and accelerates report generation. The system is expected to address the limitations of manual processes, facilitate administrative tasks for staff, and enhance public services. By implementing this system, village-level administrative services can become faster, more transparent, and better organized.